Pelayanan Kesehatan Ibu Hamil di UPT Puskesmas Melayu Kota Piring - Siti Anugerah; Hetty Ismainar; Jumrah Jumrah (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
The achievement of maternal health services at UPT Puskesmas Melayu Kota Piring has declined significantly over the past three years, with coverage dropping to 40.2% in 2025, far below the national SPM target of 100% and the regional Renstra target of 91.64%. This gap highlights inconsistencies between the required standards of integrated antenatal care and actual service delivery. This residency activity aimed to identify the root causes of low maternal health service coverage and formulate feasible solutions to improve program performance. A qualitative method was applied using a problem-solving design supported by root cause analysis. The activity was conducted from 13–30 October 2025 at UPT Puskesmas Melayu Kota Piring. Informants included the Head of Puskesmas, cluster coordinators, and midwife networks selected purposively. Data were collected through in-depth interviews, observations, and document reviews, validated using source and method triangulation, and analyzed using the problem-solving cycle. The findings indicate that the main contributors to low coverage include low K1 visits, limited maternal knowledge about first-trimester ultrasound, unintegrated recording systems, cultural beliefs, and discrepancies between BPS projection data and actual field data. The proposed interventions include health education at the Office of Religious Affairs (KUA), strengthening data recording networks, socializing the importance of first-trimester ultrasound, arranging K6 visit schedules during the first contact, and adjusting target indicators. In conclusion, improving maternal health service coverage requires cross-sector collaboration, continuous education, and strengthened recording systems to ensure that antenatal care is delivered in accordance with standards